The Foundations of Contemporary Composing - Mahnkopf, Claus-Steffen (Hofheim Wolke, 2004)
The goal of this volume is to appraise, on a theoretical and artistic level, the foundations of contemporary composition, whereby by contemporary the recent past and direct present was understood. The following reasons were decisive in choosing this topic: a) the musicological research in the domain of new music is concentrated on the now historical preiod from ca. 1950 to 1970; b) writings about contemporary music since the 1980s have been increasingly lacking in seriousreflection an d theoretical perspective; c) a clearly perceptible transformation from a First to a Second Modernity, obscured by the postmodern phenomenon and now awaiting serious critical appraisal, should be supported, above all in view of its artistic and creative potentials; and d) finally, the increasing pluralization of the discourse of contemporary composition demands a dialogical confrontation of divergent approaches.In The Foundations of Contemporary Compoising, the composers and musicologists, along with one philosopher and one interpreter explore the terrain of contemporary composition in a systematic fashion. These researches are presented in four sections: categories (Progressm reflection, deconstruction, conceptuality), material and form (Harmony, polyphony, spectralism), technology (algorithmic and electroacoustic composition, Sound composition), and interdisciplinary reflection/ contemporary performance practice. The contributors to this volume are the following: Mark André, Sebastian Claren, Frank Cox, Gunnar Hindrichs, Wieland Hoban, Claus-Steffen Mahnkopf, Barbara Maurer, Johannes Menke, Chris Mercer, Nicolai Sani, Anne Sedes, and Steven Kazuo Takasugi.
Keywords: 20th Century (1901-2000); Composing